Dietary amino acids intake and all-cause and cause-specific mortality: results from the Golestan Cohort Study - Asieh Mansour; Sayed Mahmoud Sajjadi-Jazi; Maryam Mirahmad; Pooria Asili; Maryam Sharafkhah; Sahar Masoudi; Hossein Poustchi; Akram Pourshams; Maryam Hashemian; Azita Hekmatdoost; Reza Malekzadeh (Nutrition Journal)
Abstract Background Less is known whether the amino acid composition of dietary protein sources effects on long-term health outcomes. We aimed to evaluate the association between dietary amino acid composition and all-cause and cause-specific mortality. Methods This study used data from the Golestan Cohort Study, which was performed in the Golestan Province of Iran from January 2004 to June 2008. Mortality, which was the primary outcome, was ascertained through September 2022. The Cox proportional hazards regression models were used to determine the adjusted hazard ratios (HR) and 95% confidence intervals (CI) for mortality according to the quintiles of amino acid consumption, taking the third quintile as the reference. Results A total of 47,337 participants (27,293 [57.7%] women) with a mean (standard deviation) age of 51.9 (8.9) years were included. During a median follow-up of 15 years, 9,231 deaths were documented. Regarding essential amino acid intakes, the HRs of all-cause mortality were 1.16 (95% CI, 1.07–1.26) in the first quintile, compared with the reference group (P for non-linear trend < 0.001). Similarly, non-linear associations were observed between risk of all-cause mortality and intake of branched-chain, aromatic, sulfur-containing, or non-essential amino acids (P for non-linear trend < 0.001 for all comparisons), with higher HRs for participants in the first quintiles. There was an age interaction for the associations between dietary amino acids and mortality (P for interaction ˂0.05). While high amino acid diets were detrimental in middle-aged adults (< 65 years), increased hazards of mortality were observed among older adults (≥ 65 years) with low amino acid intake. Conclusions This study showed the non-linear trend between amino acids intake and risk of mortality in the middle-aged and older Iranian population. Overall, our findings suggest that diets lower in amino acids were associated with increased hazards of mortality, particularly among older adults.